\(Ceropegia vietnamensis \) (Asclepiadoideae, Apocynaceae), a new species from Vietnam - Truong Luu, Hong; Son Le, Van; Nguyen, Phi Nga (Academia Journal of Biology, 2022)
Ceropegia vietnamensis is described as a new species from Binh Chau - Phuoc Buu Nature Reserve in the Xuyen Moc district of Ba Ria- Vung Tau province. It is morphologically close to Ceropegia laotica in general appearance and coloration of flowers but differs in many vegetative and reproductive characteristics and grows in a different habitat. The new taxon is described, illustrated with field photographs of detailed botanical characteristics and compared to related species.